(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Assessing the knowledge, attitude and practice of prehospital emergency in Vietnam in 2023. Subjects and methods: A survey on 10,800 people was implemented to assess the status of prehospital emergency and the capacity of the local health system. Results: Only 33.65% of people knew about emergency calls and 33.20% of people did not know or sure about emergency calls. 49.48% of people believed that ambulances are useful, medical staff are useful in emergency care (50.04%). All residents estimated the ambulance’s time of arrival after calls around 5 - 60 minutes. The majority of people chose to transport emergency patients by taxi, personal car or carrying patients to the hospital, only 32.63% of people chose to call an ambulance when at home and 33.80% when outside. Most people reported to trust emergency medical service workers when the ambulance arrived at the scene or when the patient was hospitalized. Conclusion: Although people’s knowledge and attitude towards prehospital emergency were inadequate, most people trusted medical staff when they arrived at the emergency scene or when taking patients to the hospital.